The Prognostic Significance of the Number of Lymph Nodes Removed from Tumor-Free Axilla in Patients with Breast Carcinoma - Can, Mehmet Fatih; Görgülü, Semih; Yağcı, Gökhan; Açıkel, Cengiz Han; Uzar, Ali İhsan; Peker, Yusuf; Tufan, Turgut (Fırat University, 2007)
Objectives: It has been made several suggestions in literature concerning with the numbers of lymph node should be examined for patients with nodenegative breast carcinoma. In the present study, we evaluated affect of number of lymph nodes removed on patients’ survival in breast cancer with negative axillary involvement status. Material and Methods: The medical records of one hundred and thirty consecutive patients with lymph node negative breast cancer who underwent axillary dissection between January 1995 and January 2000 were retrospectively reviewed. The patients were divided into two groups according to the number of lymph node (Group I ≤ 15, Group II > 15) examined. Furthermore, factors affecting survival were analyzed for those patients. Results: There were fifty-eight patients (44.6%) in Group I and seventy-two patients (55.4%) in Group II. Mean follow-up time was 7.6±1.7 years. Average survival time was 141 months for both groups. In group I and in group II overall survival rates were 89.7% and 97.2%, respectively. Despite overall survival rate was lower than group II, the difference was found not to be statistically significant (p=0.074). Primary tumor size was only factor which was found to be associated with mortality. Conclusion: We have detected any difference in survival with the harvesting of neither less nor more number of tumor-free axillary lymph nodes than 15, and we believe that performing agressive dissection is not necessary to prevent a misstaging. Furthermore, the mortality risk significantly increases with higher T stage in those cases. ©2007, Firat University, Medical Faculty

Giriş: Meme kanserli aksiller lenf nodu negatif hastalarda incelenen aksiller lenf nodu sayısının sağ kalım süresi ile ilişkisi konusunda farklı görüşler mevcuttur. Geniş aksiller diseksiyon öneren çalışmalarda asgari incelenmesi gereken lenf nodu sayısı konusunda da görüş birliği yoktur. Bu çalışmada, lenf nodu negatif hastalarda incelenen lenf nodu sayısı ile sağ kalım süresi ilişkisi ve sağ kalıma etkili diğer faktörler incelenmiştir. Gereç ve Yöntem: Meme kanseri nedeniyle 1995-2000 yılları arasında opere edilip patolojik incelemede pozitif aksiller lenf nodu saptanmayan 144 hastadan, takipte kalan ve dahil edilme kriterlerine uyan 130’una (%90.2) ait veriler incelendi. Hastalar 15 ve altı (Grup I) ile 16 ve üstü (Grup II) lenf nodu diseke edilenler olarak iki gruba ayrıldı. Gruplar sağ kalım süreleri açısından karşılaştırıldı ve tüm hastalar olası prognostik faktörler açısından incelendi. Bulgular: Hastaların 58 (%44,6)’inde 15 ve altı lenf nodu, 72 (%55.4)’inde 16 ve üstü lenf nodu diseke edilmişti. Ortalama takip süresi 7.6±1.7 yıl idi. Her iki grup için ortalama sağ kalım süresi 141 ay ve takip süresinde overall survival oranı grup I için %89.7, Grup II için %97.2 idi. Grup I’de overall survival oranı daha düşük olmakla birlikte fark anlamlı değildi (p=0.074). Tümör boyutu prognoza etkili tek faktör olarak saptandı. Sonuç: Çalışmamız 15’den az ve çok lenf nodu çıkarılan hastalar arasında sağ kalım açısından istatistiksel olarak anlamlı fark bulunmadığını göstermiştir. Bu sonuç meme kanserli hastalarda yeterli aksiller değerlendirme/sağaltım gereksinimini sağlayacak ancak kol morbiditesi açısından agresif olmayan bir aksiller diseksiyonun yeterli olduğunu düşündürmektedir. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Aksiller Lenf Nodu Negatif Meme Kanserli Hastalarda Çıkarılan Lenf Nodu Sayısının Prognostik Önemi